Odessa Sea - Cussler, Clive; Cussler, Dirk; Brick, Scott (New York : Penguin Audio, 2016)
A desperate attempt in 1917 to preserve the wealth and power of the Romanov Empire. A Cold War bomber lost with a deadly cargo. Mysterious deaths on the Black Sea linked to modern day smugglers of nuclear materials. At the center of it all is Dirk Pitt and his team from NUMA: as the danger escalates, there's only one man who can avert catastrophe.
Keywords: Pitt, Dirk (Fictional character) -- (Fictitious character) -- Fiction; Marine biologists -- Fiction; Underwater exploration -- Fiction; Audiobooks; Action and adventure fiction; Thrillers (Fiction)